Will AI Cure Cancer in Our Lifetime? A Professional and Academic Perspective - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The question of whether AI will cure cancer in our lifetime is one that captures the public imagination and drives billions in research funding. It is a ques...
Keywords: Drug Discovery; Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation